PENGARUH MEDIA PETA KONSEP DAN MINAT MAHASISWA TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH KIMIA UMUM-I - Freddy Tua Musa Panggabean; Nora Susanti (LPPM Universitas Negeri Medan, 2015)
Abstract Stoichiometry is one of the subjects in the general chemistry-I course,which has a fairly extensive study, laden with concepts and abstract. Stoichiometrywould be more appropriately taught using concept maps media so that studentseasily understand and make lectures more meaningful. In addition to the use ofconcept maps media, other factors also affect the learning outcomes of studentsis learning interest of students. In this research, comparison of the results ofstudying chemistry among the group of students who are taught by the mediamap concept with a group of students who are taught without media concept map interms of student learning interest. The final conclusion is that: (1) there issignificant influence media use of concept maps to the learning outcomes of studentson the subject of chemical stoichiometry where the average results of studying chemistry students are taught using concept maps media is higher than studentlearning outcomes are taught without using the media map concept; (2) there issignificant influence on the students' interest in learning outcomes of students onthe subject of chemical stoichiometry where the average results of studyingchemistry students who have a high interest in learning was higher than the resultsof studying chemistry student who has a low learning interest; (3) there is nosignificant effect of interaction between media use of concept maps and the interestof student learning to the learning outcomes achieved chemistry student on thesubject of stoichiometry.